ETL with Azure cookbook : practical recipes for building modern ETL solutions to load and transform data from any source /: practical recipes for building modern ETL solutions to load and transform data from any source. (2020) - Cote, Christian; Lah, Matija; Saitakhmetova, Madina
No abstract available